Students’ Feedback to Senior High School Teachers’ Performance - Anggraini Thesisia Saragih; Nora Ronita Dewi; Bela Azzura Syahmar Marpaung (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to analyze the students’ feedback to the teachers’ performance in teaching recount text. This study was conducted by descriptive qualitative method through phases; gathering information and data and analyzing data. The subject of this research was at eighth grade students of SMP Negeri 35 Medan. The instruments for collecting data were students’ written feedback and questionnaire. The data then was analyzed by using checklist.. The results of the data analysis showed that there were 62,97% of students’ used the negative feedback in giving their opinions. There were only four of twenty seven students that could enclose at least five indicators of a good feedback.